2018
DOI: 10.1016/j.matlet.2018.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-like CdS nanoparticles anchoring onto porous NiO nanoplates for enhanced visible-light photocatalytic properties

Abstract: Novel CdS/NiO nanocomposites assembled by satellite-like CdS nanoparticles anchoring onto porous NiO nanoplates have been fabricated by a step synthesis process, which involves a chemical bathing method followed by a heat treatment, and a microwave-assisted aqueous chemical reaction. The structure and photocatalytic properties of products were characterized by various techniques. More significantly, benefiting from the synergistic effect of CdS/NiO heterojunction, the as-prepared CdS/NiO architectures exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Thus, we can say that among the ROS the hydroxyl radical (OH*) contributed mostly in the degradation process. Thus, we have concluded that active radicals (*O 2 – , h + , and OH*) can collectively degrade dyes into fragmented molecules (H 2 O and CO 2 ) which is proposed in Figure b. , …”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, we can say that among the ROS the hydroxyl radical (OH*) contributed mostly in the degradation process. Thus, we have concluded that active radicals (*O 2 – , h + , and OH*) can collectively degrade dyes into fragmented molecules (H 2 O and CO 2 ) which is proposed in Figure b. , …”
Section: Resultsmentioning
confidence: 82%
“…Thus, we have concluded that active radicals (*O 2 − , h + , and OH*) can collectively degrade dyes into fragmented molecules (H 2 O and CO 2 ) which is proposed in Figure 8b. 68,69 Recyclability of the Catalyst. We studied the reusability of the catalyst because it is a very important parameter in industries.…”
Section: ■ Results and Discussionmentioning
confidence: 99%